Shuxuening injection, derived from Ginkgo biloba leaf, induced pseudo-allergic reactions through hyperactivation of mTOR - Lianmei Wang; Jingzhuo Tian; Suyan Liu; Yanyan Zhang; Jing Liu; Yan Yi; Chunying Li; Yong Zhao; Yushi Zhang; Jiayin Han; Chen Pan; Guiqin Li; et al. (Taylor & Francis Group, 2020)
Context Shuxuening injection (SXNI), derived from the leaf of Ginkgo biloba L. (Ginkgoaceae), is widely used to treat cardio-cerebral vascular system related disease due to the efficacy of dilating the blood vessels and improving the function of microcirculation. Nevertheless, SXNI induces immediate hypersensitivity reactions in clinics and the molecular mechanisms are unknown. Objective The present study investigates the molecular mechanism of SXNI mediated hypersensitivity reactions. Materials and methods Naive male ICR mice (n = 10) were administered (i.v.) with negative control combined with Evans blue (EB) (CTL-EB), SXNI (14 or 70 mg/kg) combined with EB (SXNI/1-EB or SXNI/4-EB), vascular leakage was evaluated, ears and lungs were collected for histopathological analysis. In vitro, TSC1 was knockdown in human umbilical vein endothelial cells (HUVECs). HUVECs were incubated with SXNI, and the alterations of endothelial cell permeability were observed. Rapamycin (mTOR inbibitor) was used to investigate SXNI-induced hypersensitivity reactions both in mice and HUVECs. Results SXNI (70 mg/kg) induced vascular leakage in mice. Slight oedema and microvascular dilation in the ears, and broaden of alveolar septal and monocyte infiltration in the lungs were observed in SXNI (70 mg/kg) treated mice. mTOR inhibitor alleviates SXNI mediated vascular endothelial hyperpermeability both in vitro and in vivo. Discussion and conclusions SXNI stimulates pseudo-allergic reactions through hyperactivation of mTOR signalling pathway. Our work provides the new molecular mechanism of drug related pseudo-allergic reactions, and a potential drug to prevent and treat SXNI mediated hypersensitivity reactions.